Nasolabial Cyst Associated with Odontogenic Infection - Eveline Claudia Martini; Fabiana Madalozzo Coppla; Eduardo Bauml Campagnoli; Marcelo Carlos Bortoluzzi (Hindawi Limited, 2016)
The nasolabial cyst or Klestadt cyst is a relatively uncommon nonodontogenic cyst that develops in the nasal alar region; it has uncertain pathogenesis. This lesion has slow growth and variable dimensions and is characterized clinically by a floating tumefaction in the nasolabial fold area around the bridge of the nose, causing an elevation of the upper lip and relative facial asymmetry. Diagnosis is primarily made clinically; if necessary, this is complemented by imaging. This paper reports the case of a 39-year-old male patient who complained of pain in the right upper premolar region and poor aesthetics due to a firm tumor in the right wing of the nose. Initially, this was thought to be due to an odontogenic abscess; however, the differential diagnosis was that a nasolabial cyst was communicating with the apex of teeth 14 and 15. Surgical treatment was carried out, followed by histopathological examination and concomitant endodontic treatment of the teeth involved.